Word-Problem-Solving Strategy for Minority Students at Risk for Math Difficulties. (August 2016) - Kong, Jennifer E.; Orosco, Michael J.
Minority students at risk for math difficulties (MD) struggle with word problems for various reasons beyond procedural or calculation challenges. As a result, these students require support in reading and language development in addition to math. The purpose of this study was to assess the effectiveness of a math comprehension strategy based on a dynamic assessment (DA) framework, which provided scaffolding support based on the student's reading and language levels. A multiple baseline design was used to assess eight third-grade minority students at risk for MD. As compared with the baseline phase, the strategy increased problem-solving ability for all participants. All students maintained performance levels during follow-up sessions. Results suggest that the intervention facilitated word-problem-solving performance.